Pressure-Modulated Host–Guest Interactions Boost Effective Blue-Light Emission of MIL-140A Nanocrystals - Zhang, Ting; Liang, Jiaju; Qiao, Ruidong; Yang, Binhao; Yuan, Kaiyan; Wang, Yixuan; Liu, Chuang; Liu, Zhaodong; Yang, Xinyi; Zou, Bo (Nano-Micro Letters, 2025)
Luminescent metal–organic frameworks (MOFs) have garnered significant attention due to their structural tunability and potential applications in solid-state lighting, bioimaging, sensing, anti-counterfeiting, and other fields. Nevertheless, due to the tendency of 1,4-benzenedicarboxylic acid (BDC) to rotate within the framework, MOFs composed of it exhibit significant non-radiative energy dissipation and thus impair the emissive properties. In this study, efficient luminescence of MIL-140A nanocrystals (NCs) with BDC rotors as ligands is achieved by pressure treatment strategy. Pressure treatment effectively modulates the pore structure of the framework, enhancing the interactions between the N, N-dimethylformamide guest molecules and the BDC ligands. The enhanced host–guest interaction contributes to the structural rigidity of the MOF, thereby suppressing the rotation-induced excited-state energy loss. As a result, the pressure-treated MIL-140A NCs displayed bright blue-light emission, with the photoluminescence quantum yield increasing from an initial 6.8% to 69.2%. This study developed an effective strategy to improve the luminescence performance of rotor ligand MOFs, offers a new avenue for the rational design and synthesis of MOFs with superior luminescent properties. Highlights: 1 The luminescence performance of MIL-140A is successfully improved via pressure treatment strategy with a significant increase of photoluminescence quantum yield from the initial 6.8% to 69.2%. 2 Pressure treatment boosts the host–guest interactions by inducing aperture contraction, which enhances the structural rigidity and thus enables efficient emission.